Placental weight mediates the effects of prenatal factors on fetal growth: the extent differs by preterm status - Fengxiu Ouyang; Margaret G. Parker; Sandra Cerda; Colleen Pearson; Lingling Fu; Matthew W. Gillman; Barry Zuckerman; Xiaobin Wang (2013)
Abstract Objective: Elevated pre‐pregnancy BMI, excessive gestational weight gain (GWG), and gestational diabetes mellitus (GDM) are known determinants of fetal growth. The role of placental weight is unclear. We aimed to examine the extent to which placental weight mediates the associations of pre‐pregnancy BMI, GWG, and GDM with birth weight‐for‐gestational age, and whether the relationships differ by preterm status. Design and Methods: We examined 1,035 mother‐infant pairs at birth from the Boston Birth Cohort. Data were collected by questionnaire and clinical measures. Placentas were weighed without membranes or umbilical cords. We performed sequential models excluding and including placental weight, stratified by preterm status. Results: We found that 21% of mothers were obese, 42% had excessive GWG, and 5% had GDM. Forty‐one percent were preterm. Among term births, after adjustment for sex, gestational age, maternal age, race, parity, education, smoking, and stress during pregnancy, birth weight‐for‐gestational age z ‐score was 0.55 (0.30, 0.80) units higher for pre‐pregnancy obesity vs. normal weight. It was 0.34 (0.13, 0.55) higher for excessive vs. adequate GWG, 0.67 (0.24, 1.10) for GDM vs. no DM, with additional adjustment for pre‐pregnancy BMI. Adding placental weight to the models attenuated the estimates for pre‐pregnancy obesity by 20%, excessive GWG by 32%, and GDM by 21%. Among preterm infants, GDM was associated with 0.67 (0.34, 1.00) higher birth weight‐for‐gestational age z ‐score, but pre‐pregnancy obesity and excessive GWG were not. Attenuation by placental weight was 36% for GDM. Conclusions: These results suggest that placental weight partially mediates the effects of pre‐pregnancy obesity, GDM, and excessive GWG on fetal growth among term infants.